Complex origins of the Lusitania biogeographic province and northeastern Atlantic fishes - Vítor C. Almada; Jesus Falcón Toledo; Alberto Brito; André Levy; Sergio R. Floeter; Joana I. Robalo; Joana Martins; Frederico Oliveira Almada (Frontiers of Biogeography)
The Lusitania Province encompasses the warm temperate marine waters between the southern end of the English Channel, in the North, and Cape Juby or Cape Blanco, in the South, including the Mediterranean and the archipelagoes of the Azores, Madeira and the Canary Islands. Briggs and Bowen (2012) proposed that the warm temperate provinces, although retaining their provincial status, should be grouped with the adjacent tropical ones. Thus, they included the Lusitania Province in a warm eastern Atlantic region. We argue that the time elapsed since the Miocene was sufficient to allow the evolution of endemic species, genera and some higher rank taxa, a finding that emphasizes the convenience to avoid the integration of the province in this larger region. The tropicality index for the Lusitania Province is 1.82, indicating a prevalence of warm water over cold water fish. However, this value is strongly biased by the large differences between the Macaronesian archipelagos (4.08) and the mainland coasts of the Lusitania Province (0.66).